The Role of Parents' Empathic Tendencies in Children Value Acquisition - Yakupoğulları, Ayşe; YAĞAN, SEVCAN (Anı Yayıncılık, 2020)
Purpose: The present study aims to reveal the predictive role of parents' empathic tendencies in children value acquisition. Research Methods: We conducted a relational survey study, including 170 children aged 60-72 months, 85 of whom were girls and 85 were boys, who were attending the kindergarten school in Malatya City, and their parents. The Pre-school Values Scale Student Form, Empathy Tendency Scale and Sociodemographic Information Form were used to collect data. Findings: Results indicated that there was a significant positive correlation between value of children and parent’s empathic tendencies. As empathic and sympathetic tendencies of parents increased, the children's respect, honesty, responsibility, cooperation, friendship and sharing scores increased. The findings showed that the values which had the highest average score were sharing, respect and honesty among the study group. Although the mean total empathy level of the mothers was higher than the fathers’, it was found that father empathy level was positively related with the child value levels, suggesting that the fathers had important role in child value education. Implications for Research and Practice: Parent training can be organized to increase the empathy skills of the families. Besides, different studies can be carried out to examine the factors affecting children’s value acquisition.
Çocukların Değer Edinimlerinde Ebeveynlerin Empatik Eğilimlerinin Rolü
Çocukların Değer Edinimlerinde Ebeveynlerin Empatik Eğilimlerinin Rolü
Keywords: Value; Empathy; Parent; Children